2020
DOI: 10.1155/2020/3891343
|View full text |Cite
|
Sign up to set email alerts
|

Model Test on Bearing Characteristics of Basalt Fiber‐Reinforced Concrete Lining

Abstract: Adding fiber can improve the brittleness of plain concrete. Compared with plain concrete, basalt fiber-reinforced concrete has the advantages of strengthening, toughening, and crack resistance. Compared with steel fiber-reinforced concrete, basalt fiber-reinforced concrete has better construction performance. Basalt fiber concrete is a type of inorganic material with environmental protection and high mechanical properties, which has an important mechanical advantage for controlling the deformation of the soft … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…At present, some scholars have studied the anti-fault measures, which mainly propose two ways of anti-seismic joints and flexible joints, to study the anti-fault measures in tunnels. Current scholars on the application of fiber concrete in tunnel lining have been part of the study, such as Wang [8], etc. Through the reinforced concrete and basalt fiber concrete lining indoor mechanical properties model test, the study of basalt fiber concrete lining bearing characteristics found that basalt fibers help to improve the lining of the initial bearing performance, compared with reinforced concrete, which is more conducive to controlling the deformation of the tunnel of the weak surrounding rock.…”
Section: Introductionmentioning
confidence: 99%
“…At present, some scholars have studied the anti-fault measures, which mainly propose two ways of anti-seismic joints and flexible joints, to study the anti-fault measures in tunnels. Current scholars on the application of fiber concrete in tunnel lining have been part of the study, such as Wang [8], etc. Through the reinforced concrete and basalt fiber concrete lining indoor mechanical properties model test, the study of basalt fiber concrete lining bearing characteristics found that basalt fibers help to improve the lining of the initial bearing performance, compared with reinforced concrete, which is more conducive to controlling the deformation of the tunnel of the weak surrounding rock.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with steel fiber and carbon fiber, BF has the advantages of excellent mechanical properties, outstanding thermal properties, stable chemical properties, and excellent compatibility. Therefore, the study of BFRC has certain theoretical significance and practical value, and also plays an important guiding role in improving the performance of concrete [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…ere are three main types of approaches for the analysis of seismic performance of underground structures: field investigations, model tests, and numerical simulations [8][9][10][11][12][13]. Numerical simulation methods have been widely used to analyse the dynamic response of tunnel structure in some bad conditions, but the computational ability of computers and the mechanical models needs to be studied further in the existing software.…”
Section: Introductionmentioning
confidence: 99%